Developing blockchain-based business globally - Šilenskytė, Aušrinė (Henry Stewart Talks, 2023)
Blockchain, Cryptocurrency, Initial Coin Offerings (ICO), Decentralized Applications (DApps), Tokens, Virtual community, Global policy, Regulations, Banks